Canopy gaps formed by mangrove trimming: an experimental test of impact on litter fall and standing litter stock in Southwest Florida (USA) - Ellis, William L.; Bell, Susan S. (Journal of experimental marine biology and ecology, 2004)
Mangroves in Florida (USA) are subject to horticultural pruning that may increase the size of canopy gaps and alter rates of litter production and accumulation. Mangrove canopy gap formation is a common phenomenon, known to alter abiotic conditions near the forest floor. Using a series of field experiments in Rookery Bay, Florida, the effects of mangrove trimming on canopy density, mangrove litter production, standing litter stocks, and the decomposition rate of Rhizophora mangle leaves on the forest floor were assessed. Litter trap collections over the year following mangrove trimming indicated that pruned mangrove stands (canopy coverage: 42.8±0.9%; mean±S.E.) produced approximately one-half of the litter of mangrove stands with relatively complete canopies (canopy coverage: 72.1±0.5%). However, there was no significant difference between the mass of standing litter on the forest floor beneath reduced canopy and intact canopy mangroves. Also, R. mangle leaves held on the forest floor in fiberglass litter bags at both reduced canopy and control sites did not decompose at different rates over 28 days. These results indicate that while system-wide mangrove litter production should be reduced by the formation of these gaps in mangrove forests, postproduction influences may obscure any site-specific declines in standing litter stocks.